Governmental Insensitivity to Accountability: Effects and Consequences for the ZANU Pf Led Administration in Zimbabwe - Chikerema, A. F; Chakunda, V (African Society for Research on the Education of Adults, 2023)
Government accountability to its citizens is a critical factor in development. Lack of government accountability is associated with citizen disloyalty and confrontations which may affect the economic and political situation in a country. This paper examined the effects of lack of accountability on the part of the ZANU PF led government in Zimbabwe. The established lack of sufficient government accountability in Zimbabwe has birthed an unprecedented unemployment rate of 96%. Informalization of the economy which has led to citizens surviving on being vendors has seen the competency of the government being put in question notwithstanding the political instability within the ruling. The internally fragmented ZANU PF had to suffer the effects of opposition politics, and pressure from social movement such as Tajamuka, Zimbabwe Shutdown. The Beitbridge border protest epitomised the displeasure of the citizenry; it also symbolizes an eco-political war against the Mugabe-led ZANU PF government. This paper adopted a desk research approach, due to its nature it utilised secondary sources such as newspaper articles, journal articles, commentaries and textbooks to conceptualize the problem under investigation. The study established that the insensitivity by the ZANU led government received a serious backlash which was an effort of bringing government to answer for its incompetence. On an overall note protests in Zimbabwe have been inspired by internalized anger and the undeterred interest to alter the political realities for the better, this time around with the citizens backed by social media to mobilize themselves fashionably. In future there is need for the government to necessitate a bottom up approach in its implementation statutes so as to involve the citizens in all levels of decision making.